The Struggle of Becoming the 11th Member State of ASEAN: Timor Leste's Case - Windraskinasih, Mutiara; Afriansyah, Arie (Brawijaya Law Journal, 2018)
In March 4, 2011, Timor Leste applied for membership in ASEAN through formal application conveying said intent. This is an intriguing case, as Timor Leste, is a Southeast Asian country that applied for ASEAN Membership after the shift of ASEAN to acknowledge ASEAN Charter as its constituent instrument. Therefore, this research paper aims to provide a descriptive overview upon the requisites of becoming ASEAN Member State under the prevailing regulations. The substantive requirements of Timor Leste to become the eleventh ASEAN Member State are also surveyed in the hopes that it will provide a comprehensive understanding as why Timor Leste has not been accepted into ASEAN. Through this, it is to be noted how the membership system in ASEAN will develop its own existence as a regional organization. This research begins with a brief introduction about ASEAN's rules on membership admission followed by the practice of ASEAN with regard to membership admission and then a discussion about the effort of Timor Leste to become on eof ASEAN member state.